Choline hydroxide, an efficient, green, and recyclable base catalyst, promoted the synthesis of 3-aroylflavones via Baker–Venkataraman rearrangement - Minh Thi Nguyen; Chi-Tam Vo; Quoc-Huy Bui; Tung-Phong Dinh; Thi Xuan Thi Luu (Green Chemistry Letters and Reviews)
3-Aroylflavones, a new synthesized group of flavones, have been recently studied via Baker–Venkataraman rearrangement under ‘one-pot’ or sequential ‘one-pot’ reaction conditions. Choline hydroxide, an inexpensive, easily prepared, and green homogeneous catalyst has been found to be the most efficient catalyst among several base catalysts such as KOH/pyridine, KOH/triethylamine, and CaO-ES/triethylamine in the sequential ‘one-pot’ synthesis of 3-aroylflavones. Moreover, the catalyst’s efficiency, and high recyclability to six times without considerable loss of 3-aroylflavones have enhanced the importance of the procedure. Furthermore, 1D-NMR, 2D-NMR, and HRMS have also been used to elucidate the structures of synthesized compounds.